ANALISIS PENDAPATAN DAN TATANIAGA BERAS VARIETAS PANDAN WANGI DAN VARIETAS UNGGUL BARU (Kasus Kelompok Tani Nanggeleng Jaya Desa Songgom Kecamatan Gekbrong Kabupaten Cianjur Provinsi Jawa Barat)ANALISIS PENDAPATAN DAN TATANIAGA BERAS VARIETAS PANDAN WANGI DAN VARIETAS UNGGUL BARU (Kasus Kelompok Tani Nanggeleng Jaya Desa Songgom Kecamatan Gekbrong Kabupaten Cianjur Provinsi Jawa Barat) - Yunita, Ima; Yusdiarti, Arti; Nahraeni, Wini (JURNAL AGRIBISAINS, 2015)
ABSTRACTThe purpose of this research is to determine the pandan wangi rice and new prime varieties riceÂ farmerâs income, the marketing channel, the marketing margin, the farmers share, as well as theÂ ratio of benefits and costs. The results showed that pandan wangi rice farmerâs income perÂ season is more than the farmers of the new prime varieties rice, while the pandan wangi varietiesÂ farmerâs income per year less than the new prime varieties rice farmers. There are 5 channels ofpandan wangi rice marketing, while there are 7 channels of new prime varieties rice marketing.Â Marketing functions of pandan wangi and the new prime varieties rice differ in the level ofÂ collector. The marketing margin, farmerâs share, cost and benefit ratio of pandan wangi riceÂ varieties which have the largest are in the marketing channel 1, 5, and 1. The marketing margin,Â farmerâs share, cost and benefit ratio of new prime varieties rice which have the smallest valuesare in the marketing channel 5, 1, and 5. The marketing margin, farmerâs share, cost and benefitÂ ratio of the new prime varieties rice that have the largest are in the marketing channels 1, 4, andÂ 7. The marketing margin, farmerâs share, cost and benefit ratio of new prime varieties rice whichhave the smallest values are in the marketing channels 4, 1, and 6Key words: Income, marketing, pandan wangi varieties, new rice varieties